Eksplorasi Faktor-Faktor yang Mempengaruhi Minat Belajar Siswa Pada Mata Pelajaran PPKn - asriyah, ismatul; Rofiqi, Ahmad Zaki; Mas'odi, Mas'odi; Imamah, Siti Nur (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2024)
This research aims to determine factors that can increase students' interest in learning in Civics subjects. The type of research used in this research is qualitative research using qualitative descriptive methods. The data collection used was observation, interviews and literature study. In the learning process, a student's interest in learning is very important in the teaching and learning process, because if a student has low interest in learning, it will be difficult for him to receive knowledge from the teacher, so that learning outcomes will be less effective. The main factor that influences students' interest in learning is themselves, especially interest, talent, motivation, especially in Civics subjects. Civics is a subject that often uses the lecture method, which makes students quickly get bored with the method used by the teacher. As a professional teacher, the teacher must be able to apply a learning method or model that suits the student's personality as an attraction to increase student interest in learning. Another factor that influences students' interest in learning comes from parents as a circle of friends in providing stimulus to children, apart from that it also comes from the school and surrounding environment. Proper and continuous stimulus from parents can give rise to positive encouragement for children to be more diligent and active in learning